Community-Based Stunting Intervention Strategies: Literature Review - Rasdiyanah; Kusumawardani, Lita Heni; Rachmawati, Utami; Jauhar, Muhammad; Rohana, I Gusti Ayu Putu Desy (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Stunting is a growth disorder in children caused by malnutrition for a long time. The child's conditionbecomes shorter than normal children his age and has a delay in thinking. The incidence of stunting inIndonesia is quite high sostunting is becoming a priority health problem now. An effective strategy isneeded to control stunting in Indonesia. The aim of this review was to explore the stunting managementstrategies to potentially implement in Indonesia. A literature review design was used to explore the stuntingmanagement strategies. Literature study of 15 articles retrieved from the journal database of ScienceDirect, Proquest, Scopus, and EBSCO in the last 5 years using keywords stunting, management, ruralareas, and community based. Data were analyzed in tables consist of title, author, year, sample,methodology, and result. Control and preventionstunting could done through integrated nutritioninterventions. Strategy Specific nutritional interventions such as providing supplementation andsupplementary food plus nutritional interventions including non-health interventions, improving thefamily's economy, access and utilization of clean water, sanitation (especially latrines and safe septictanks), which are urgently needed to support personal hygiene behavior and the environment .Interventions can use mother's counseling and support methods regularly by health workers by involvinghealth cadres. Specific and sensitive intervention strategies are effective strategies within stunting controland prevention. Monitoring and evaluation of nutritional knowledge, attitudes and practices coupled withan assessment of the nutritional status and morbidity of mothers and children is also very necessary incontrolling and preventing stunting in Indonesia.